The Influence Of Internal And External Factors On Fast Food Consumption Intentions Among Undergraduate Culinary Education Students: A Cross Sectional Study - Putri Febri Wahyuningtiyas; Sri Handajani; Any Sutiadiningsih; Hidayatun Muyasyaroh (Universitas Negeri Padang, 2026)
This study aims to analyze the influence of internal and external factors on the interest in consuming fast food among undergraduate students of Culinary Arts Education (UNESA). This study uses a quantitative approach with a cross-sectional survey design involving 90 respondents selected through random sampling techniques from a population of 870 students. Data collection was carried out using a structured questionnaire with a 4-point Likert scale and analyzed using multiple linear regression. The results showed that internal factors had a positive and significant effect on consumption interest (Sig. 0.036 < 0.05), with lifestyle indicators as the dominant factor. External factors also had a positive and very significant effect (p < 0.001), with location and ease of access as the most dominant factors. Simultaneously, internal and external factors had a significant effect on fast food consumption interest with a coefficient of determination (R2) of 0.517. and a Cohen's f2 value of 1.070 indicating a large effect size. This means that 51.7% of the variation in consumption interest can be explained by the model. The regression equation obtained is Y = -2.063 + 0.204X₁ + 0.348X₂, which indicates that external factors have a stronger influence than internal factors. This finding indicates that a practical lifestyle and ease of environmental access are the main factors in shaping students' fast food consumption behavior. This finding indicates that although students will later have a deep understanding of nutrition and culinary fields, external environmental factors such as location and ease of access remain the main determinants that are stronger in shaping their fast food consumption behavior.